Implementation of Clinical Supervision for Islamic Religious Education Subject Teachers at MIN I Pamekasan - Abdul Hannan (Penerbit Presisi Pustaka, 2026)
This study examines the implementation of clinical supervision by madrasah principals for Islamic Religious Education (PAI) teachers at MIN Pamekasan. MIN 1 Pamekasan is a high-achieving madrasah with numerous awards. The research context is fourfold: 1) How to prepare for the implementation of clinical supervision, 2) How to implement clinical supervision, and 3) How to evaluate the implementation of clinical supervision for Islamic Religious Education (PAI) teachers. This study employed a qualitative approach. Data collection was conducted through three techniques: unstructured interviews, non-participant observation, and documentation. Informants in this study consisted of madrasah principals and Islamic Religious Education (PAI) teachers. The data analysis technique used was a flow model analysis, which encompasses the stages of data collection, data reduction, data presentation, and verification or drawing conclusions. The results of this study are: First: Preparation, which included socialization activities to align perceptions between supervisors and teachers, developing instruments, pre- and post-observation interview guidelines, developing an implementation schedule, and meetings leading up to the clinical supervision. Second: The implementation stage of clinical supervision. The principal enters with the PAI teacher who will be supervised without explaining to the students about the principal's presence in the classroom, the principal occupies a position that does not have the potential to disrupt the learning process, the principal focuses on the learning process, checks the activities contained in the instrument according to the real conditions of the learning process, and writes down important notes that are not yet on the instrument. Third: The evaluation stage is realized in two activities (a) meetings conducted individually in the principal's office, (b) meetings in order to improve the competence of PAI teachers according to the results of clinical supervision.